Effect of biotic and abiotic factors on the content of flavonoids in leaves of Passiflora sp. L.: A systematic review - Mateus-Maldonado, Juan Felipe (2023)
The genus Passiflora accounts for 17% of global flavonoid production, and several strategies have been explored to increase their production in these plants, given the growing demand for these metabolites. The aim of this study is to examine the published literature on the correlation between flavonoid concentrations in Passiflora genus leaves and factors such as microorganism presence, soil fertility, fertilizer use, soil conditioners, agronomic practices, weather patterns, and plant phenology. The search was conducted across nine databases. Web of Science, Nature, Agris, Dialnet, Scielo, Science Database-ProQuest, Scopus (Elsevier), Springer, and EBSCOhost and two search engines: Google Scholar and Semantic Scholar, obtaining 19 indexed articles. The results indicate that treatments incorporating a single biotic or abiotic factor in the crop lead to a 380% increase in the production of flavonoids at the leaf level, while the combination of different biotic and abiotic factors leads to a 491% increase in the production of this group of metabolites at the leaf level. It is essential to assess the integrated agronomic management of Passiflora sp. to increase the concentration of these metabolites in the leaves of productive branches with fully ripened fruits ready for harvest (BBCH code 89), without losing the possibility of using the current main product of the crop.